Prime Minister Decree No. 2131 of the Year 2025 - Prime Minister (The Middle East Library For Economic Services, 2025)
Thursday 26 June 2025 (AD) shall be considered an official paid holiday for the workers at ministries, government departments, public authorities, local administrative units, public sector companies, and public business sector companies, instead of the Gregorian date corresponding to the first of Muharram, 1447 (AH), according to the outcomes of sighting of the new crescent Moon, on the occasion of the beginning of the Islamic (Hijri) new year. Meanwhile, the examination works shall continue to take place according to the schedule set by the competent authority.